How to boost the European Green Deal's scale and ambition - Rafael Wildauer; Stuart Leitch; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2020)
The European Green Deal (EGD) is the European Union's flagship strategy to tackle climate change. This policy study compares the ambition and scale of the EGD with the current relevant scientific literature. The goal is to assess whether the current proposals are capable of fulfilling the EU's commitment to limit global warming to 1.5°C in line with the Paris Agreement.
Keywords: 330; EU-Umweltpolitik; Internationales Abkommen